Hard- and software of real time simulation tools of Electric Power System for adequate modeling power semiconductors in voltage source convertor based HVDC and FACTS - Ufa Ruslan A.; Sulaymanova Venera A.; Gusev Alexandr S. (MATEC Web of Conferences, 2014)
The motivation of the presented research is based on the needs for development of new methods and tools for adequate simulation of Flexible Alternating Current Transmission System (FACTS) devices and High Voltage Direct Current Transmission (HVDC) system as part of real electric power systems (EPS). For that, a hybrid approach for advanced simulation of the FACTS and HVDC based on Voltage Source is proposed. The presented simulation results of the developed hybrid model of VSC confirm the achievement of the desired properties of the model and the effectiveness of the proposed solutions.